Iron superoxide dismutases in eukaryotic pathogens: new insights from Apicomplexa and Trypanosoma structures. Issue 5 (1st May 2015) - Phan, Isabelle Q. H.; Davies, Douglas R.; Moretti, Nilmar Silvio; Shanmugam, Dhanasekaran; Cestari, Igor; Anupama, Atashi; Fairman, James W.; Edwards, Thomas E.; Stuart, Kenneth; Schenkman, Sergio; Myler, Peter J.
<x xml:space="preserve">Abstract</x> Prior studies have highlighted the potential of superoxide dismutases as drug targets in eukaryotic pathogens. This report presents the structures of three iron‐dependent superoxide dismutases (FeSODs) from Trypanosoma cruzi, Leishmania major and Babesia bovis. Comparison with existing structures from Plasmodium and other trypanosome isoforms shows a very conserved overall fold with subtle differences. In particular, structural data suggest that B. bovis FeSOD may display similar resistance to peroxynitrite‐mediated inactivation via an intramolecular electron‐transfer pathway as previously described in T. cruzi FeSOD isoform B, thus providing valuable information for structure‐based drug design. Furthermore, lysine‐acetylation results in T. cruzi indicate that acetylation occurs at a position close to that responsible for the regulation of acetylation‐mediated activity in the human enzyme.